Clinical and genomic analysis of hypermucoviscous Klebsiella pneumoniae isolates: Identification of new hypermucoviscosity associated genes - Jin, Meiling; Jia, Tianye; Liu, Xiong; Yang, Meitao; Zhang, Na; Chen, Jiali; Yang, Xiaojing; Qin, Shiyu; Liu, Fangni; Tang, Yue; Wang, Yong; Guo, Jinpeng; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Hypermucoviscous Klebsiella pneumoniae (HmKp) poses an emerging and highly pathogenic global health threat. This study aimed to investigate the clinical and genomic characteristics of HmKp isolates to better understand the virulence mechanisms of the hypermucoviscous (HMV) phenotype. Methods From May 2018 to August 2021, 203 non-repeat K. pneumoniae isolates causing invasive infections were collected from a hospital in Beijing, China. Isolates were divided into HmKp (n=90, 44.3%) and non-HmKp (n=113, 55.7%) groups according to string test results. Results Multivariate regression showed that diabetes mellitus (odds ratio [OR]=2.20, 95% confidence interval (CI): 1.20-4.05, p=0.010) and liver abscess (OR=2.93, CI 95%:1.29-7.03, p=0.012) were associated with HmKp infections. K. pneumoniae was highly diverse, comprising 87 sequence types (STs) and 54 serotypes. Among HmKp isolates, ST23 was the most frequent ST (25/90, 27.8%), and the most prevalent serotypes were KL2 (31/90, 34.4%) and KL1 (27/90, 30.0%). Thirteen virulence genes were located on the capsular polysaccharide synthesis region of KL1 strains. HmKp isolates were sensitive to multiple antibiotics but carried more SHV-type extended spectrum β-lactamase (ESBL) resistance genes (p<0.05), suggesting that the emergence of ESBL-mediated multidrug resistance in HmKp should be monitored carefully during treatment. Phylogenetic analysis disclosed that HmKp isolates were highly diverse. Comparative genomic analysis confirmed that the HMV phenotype is a plasmid-encoded virulence factor. Seventeen HmKp genes were highly associated with HmKp, and included rmpAC, 7 iron-acquisition-related genes, and pagO, which may promote liver abscess formation. Discussion This investigation provides insight into the mechanisms producing the HMV phenotype.